Liquidating bankers' acceptances: International crisis, doctrinal conflict and American exceptionalism in the Federal Reserve 1913-1932 - Marc Christopher Adam (Freie Universität Berlin, School of Business & Economics, 2020)
This paper seeks to explain the collapse of the market for bankers' acceptances between 1931 and 1932 by tracing the doctrinal foundations of Federal Reserve policy and regulations back to the Federal Reserve Act of 1913. I argue that a determinant of the collapse of the market was Carter Glass' and Henry P. Willis' insistence on one specific interpretation of the "real bills doctrine", the idea that the financial system should be organized around commercial bills. The Glass-Willis doctrine, which stressed non-intervention and the self-liquidating nature of real bills, created doubts about the eligibility of frozen acceptances for purchase and rediscount at the Reserve Banks and caused accepting banks to curtail their supply to the market. The Glass-Willis doctrine is embedded in a broader historical narrative that links Woodrow Wilson's approach to foreign policy with the collapse of the international order in 1931.
urn:nbn:de:kobv:188-refubium-26744-2
Keywords: B27; B30; E58; F34; N12; N22; 330; Federal Reserve System; Acceptances; Great Depression